Penerapan Strategi Shifting Quality yang Kurang Tepat pada 3second Jember: : Analisis Dampak Terhadap Kinerja Penjualan dan Presepsi Konsumen - Azzahro, Fauziyah; Martiana Kholila Fadhil, Martiana; Hikmah Rian Jaya, Hikmah Rian Jaya (Electronic Journal of Social and Political Sciences (E-SOSPOL), 2025)
This study aims to analyze the inappropriate implementation of the shifting quality strategy at fashion brand 3second Jember and its impact on sales performance and consumer perceptions. Using a mixed method approach with sales data for the period 2023-2024 and in-depth interviews, this research found that the shifting quality strategy implemented by 3second Jember experienced a significant implementation failure. The data showed a drastic 29.50% drop in sales from 2023 to 2024, with the largest drops occurring in June (-60.75%) and September (-66.23%). Analysis revealed that changes in quality without considering consumer perceptions and expectations led to a decline in brand trust and perceived quality. This research contributes to the strategic management literature by providing empirical evidence on the risks of implementing an immature quality shifting strategy in the Indonesian fashion retail industry